UNDERSTANDING OF RELIGIOUS MODERATION OF ISLAMIC RELIGIOUS EDUCATION TEACHERS AT MADRASAH ALIYAH AND HIGH SCHOOLS IN MAJENE REGENCY - Muhammad Irfan Syuhudi (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
Islamic religious groups, which carry radical ideologies, are not only targeting ordinary people. They also reach religious and public schools through the doctrine of Islamic Religious Education teachers. This study described the understanding and attitudes of PAI teachers in Majene regarding the diversity of religions, ethnicities, and minority groups; PAI teachers' knowledge of the relationship between Islam and the state; and the understanding of PAI teachers on defining the relationship between religion and local traditions. Using qualitative research, data collection was carried out through interviews, observations, and literature studies. Then, it was analyzed through descriptive qualitative. Informants included PAI teachers in Majene, Principal of high schools, Principal of MAN Majene, Heads of the Ministry of Religion in Majene, students, and community leaders. The findings of this study: First, PAI teachers in Majene consider religious and ethnic diversity as sunnatullah, so no need to argue. In contrast, PAI teachers show a lack of respect towards minority Islamic religious groups, especially those often disrupt Indonesian harmony. Second, PAI teachers in Majene consider that the Unitary State of the Republic of Indonesia has reached the ideal point, and Pancasila has reflected the diversity of life in Indonesia. Therefore, PAI teachers disagree with religious groups who want to establish an Islamic state (khalifah). Third, the local religious traditions in Majene community are traces of the local scholars' legacy and Islam propagators in Mandar, which are not contradicting Islamic law. The religious understanding of PAI teachers in Majene is generally moderate.